2013
DOI: 10.1002/bem.21829
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use and risk of intracranial tumors: A consistency analysis

Abstract: A meta-analysis of studies on intracranial tumors and mobile phone use published by the end of 2012 was performed to evaluate the overall consistency of findings, assess the sensitivity of results to changes in the dataset, and try to detect the sources of between-study heterogeneity. Twenty-nine papers met our inclusion criteria. These papers reported on 47 eligible studies (17 on glioma, 15 on meningioma, 15 on acoustic neuroma), consisting of either primary investigations or pooled analyses. Five combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 66 publications
2
31
0
1
Order By: Relevance
“…Among the great deal of investigations raised in recent years, at least one evidence seemingly emerged, consisting in the fact that the use of mobile phones for 10 years or longer may increase the risk of certain types of cancer [odds ratio (OR), 1.18; 95% confidence interval (95% CI), 1.04-1.34], whereas this association was mostly insignificant for normal mobile phone users compared to non-users (OR =0.98; 95% CI, 0.89-1.07) (6). Interestingly, two other recent meta-analyses concluded that long-term ipsilateral users of mobile phone have an increased risk of glioma (OR =1.46; 95% CI, 1.12-1.92) (7), whereas no significant association was found with meningioma [relative risk (RR), 0.98; 95% CI, 0.75-1.28] or acoustic neurinoma (RR =1.14; 95% CI, 0.65-1.99) in long-term mobile phone users (i.e., ≥10 years) (8). Indeed, experimental evidence was brought about potential genetic damage of RFs emitted by mobile phones in human cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…Among the great deal of investigations raised in recent years, at least one evidence seemingly emerged, consisting in the fact that the use of mobile phones for 10 years or longer may increase the risk of certain types of cancer [odds ratio (OR), 1.18; 95% confidence interval (95% CI), 1.04-1.34], whereas this association was mostly insignificant for normal mobile phone users compared to non-users (OR =0.98; 95% CI, 0.89-1.07) (6). Interestingly, two other recent meta-analyses concluded that long-term ipsilateral users of mobile phone have an increased risk of glioma (OR =1.46; 95% CI, 1.12-1.92) (7), whereas no significant association was found with meningioma [relative risk (RR), 0.98; 95% CI, 0.75-1.28] or acoustic neurinoma (RR =1.14; 95% CI, 0.65-1.99) in long-term mobile phone users (i.e., ≥10 years) (8). Indeed, experimental evidence was brought about potential genetic damage of RFs emitted by mobile phones in human cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that RF–electromagnetic fields (EMFs) negatively affect the brain. After the International Agency for Research on Cancer (IARC) classified RF-EMFs as a group 2B human carcinogen, it was reported that RF-EMFs from mobile and cordless phones were associated with the initiation and progression of malignant brain tumors [2, 3]. RF-EMFs may cause DNA damage in brain cells, which leads to altered gene expression, morphological change, and even cell death [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…assessed the intracranial tumors and cell phone use and they reported the occurrence of intracranial tumors. In addition, they stated the combined relative risk in long-term cell phone users (≥ 10 years) for meningioma 40 .…”
Section: Carcinogenic Effectsmentioning
confidence: 99%